2011
DOI: 10.1111/j.1365-2036.2011.04785.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of entecavir therapy in chronic hepatitis B patients with suboptimal response to adevofir

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…Third, for patients who received adequate anti‐viral therapy, serum ALT levels often decreased to levels below 30 U/L when there was sustained virological response . Fourth, in the current study, majority of subjects who had serum ALT levels within the ULN by current threshold were still unhealthy.…”
Section: Discussionmentioning
confidence: 62%
“…Third, for patients who received adequate anti‐viral therapy, serum ALT levels often decreased to levels below 30 U/L when there was sustained virological response . Fourth, in the current study, majority of subjects who had serum ALT levels within the ULN by current threshold were still unhealthy.…”
Section: Discussionmentioning
confidence: 62%
“…34 In addition, the size of our cohort and small number of patients in each treatment group limited the degree to which we could simultaneously investigate multiple factors predictive of a composite relapse following anti-viral discontinuation. In particular, adequate comparison of post-treatment outcomes between individual anti-viral agents and whether newer first-line agents entecavir and tenofovir are superior to lamivudine and adefovir, such as has been recently suggested, [34][35][36] was not possible. Larger cohorts will help to identify additional factors predictive of a sustained response.…”
Section: Discussionmentioning
confidence: 99%
“…Following cessation of anti-viral therapy, 21 (63%) patients had a viral relapse, 16 (48%) had a biochemical relapse and 11 patients (33%) met the primary composite end point of a biochemical and virological relapse requiring retreatment. A total of 16 patients were ultimately restarted on treatment, leaving 17 (52%) patients who remained treatment-free in the follow-up period, a median of 36 [24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Reijnders et al [27] reported that ETV was effective in ADV-experienced patients including those with ADV resistance and that there was no difference in the efficacy of ETV between LAM-naive and -experienced patients without a history of LAM resistance. Similarly, Sheen et al [28] demonstrated that, by 12 months after switching to ETV treatment, complete viral suppression (serum HBV DNA <100 IU/ml) was achieved in the majority of both LAM-experienced and -naive patients (68%) who had a suboptimal response to ADV. However, in LAM-resistant patients, ETV monotherapy reduced the probability of achieving a virologic response.…”
Section: Discussionmentioning
confidence: 99%